Formulation and Evaluation of the Physical Properties of Anti-Acne Serum Based on Ethanol Extract of Passiflora foetida L. Leaves - Elianasari Elianasari; Kiki Yuli Handayani; Agita Casanova Cava; Corona Mentari; Wanda Nurbaiti (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Passiflora foetida L. (rambusa) leaves contain bioactive compounds with potential antibacterial activity against acne-causing bacteria. This study aimed to evaluate the antibacterial effect of ethanolic extracts of P. foetida L. leaves against Propionibacterium acnes and Staphylococcus epidermidis, and to formulate and assess the physical properties of serum preparations containing the extract. Ethanolic extracts at concentrations of 5%, 10%, and 15% were tested using the well diffusion method on Mueller Hinton Agar (MHA), with positive and negative controls. Serum formulations containing 0% (F0), 5% (FI), 10% (FII), and 15% (FIII) extract concentrations were prepared and evaluated for organoleptic characteristics, homogeneity, spreadability, adhesion, pH, and viscosity. The extract demonstrated antibacterial activity against both bacteria, producing inhibition zones at 15% concentration of 5.83 mm for P. acnes and 3.69 mm for S. epidermidis. The inhibition zone diameter increased with extract concentration. All formulations showed good homogeneity, stable pH (approximately 6.0), and acceptable organoleptic characteristics. Spreadability ranged from 9.0–10.0 cm, adhesion time from 8–17 seconds, and viscosity values were 300 mPa·s (F0), 165 mPa·s (FI), 189 mPa·s (FII), and 198 mPa·s (FIII). In conclusion, the 96% ethanolic extract of P. foetida L. leaves possesses antibacterial potential against acne-causing bacteria, while the formulated serum exhibits favorable physical characteristics for topical application and potential as a functional anti-acne cosmetic product.